Boy : tales of childhood - Dahl, Roald (Great Britain Jonathan Cape, 2016)
An autobiography is a book a person writes about his own life and it is usually of all sorts of boring details. This is not an autobiography. I would never write a history of myself. On the other hand, throughout my young days at school and just afterwards number of things happened to me that i have never forgotten.
Keywords: Dahl, Roald; Authors, English